Antibacterial Activity of Cold Atmospheric Pressure Argon Plasma against 78 Genetically Different (mecA, luk-P, agr or Capsular Polysaccharide Type) Staphylococcus aureus Strains - Matthes, Rutger; Lührman, Anne; Holtfreter, Silva; Kolata, Julia; Radke, Dörte; Hübner, Nils-Olaf; Assadian, Ojan; Kramer, Axel (Skin pharmacology and physiology, 2016)
Previous studies on the antimicrobial activity of cold atmospheric pressure argon plasma showed varying effects against mecA + or mecA - Staphylococcus aureus strains. This observation may have important clinical and epidemiological implications. Here, the antibacterial activity of argon plasma was investigated against 78 genetically different S. aureus strains, stratified by mecA, luk-P, agr1-4, or the cell wall capsule polysaccharide types 5 and 8. kINPen09® served as the plasma source for all experiments. On agar plates, mecA + luk-P - S. aureus strains showed a decreased susceptibility against plasma compared to other S. aureus strains. This study underlines the high complexity of microbial defence against antimicrobial treatment and confirms a previously reported strain-dependent susceptibility of S. aureus to plasma treatment.